Brand Image, Brand Trust, Experiential Marketing and Perceived Price on Super-app Customer Purchase Decisions: Go-Jek Application User Perception - Nurchayati; Bambang Riyadi; Sartini (Publindo Akademika, 2022)
This study aims to examine customer purchase decisions through the go-jek application based on brand image, trust, experiential marketing and perceived price in Semarang City. The research population is all users of the Go-Jek application in Semarang City, with the criteria of at least 2 purchases through the Go-Jek application and a minimum age of 17 years. The sample of this research was 100 respondents through purposive sampling. The hypothesis testing was conducted by using Linear Regression with Partial Least Square (PLS)-based SEM tools. The results showed that experiential marketing and perceived price positively and significantly affect purchase decisions. In contrast, brand image and trust do not significantly affect the purchase decision. It confirms that purchasing decisions are influenced by experiential marketing and perceived reputable prices in customers of the Gojek super-app. The results highlight the importance of experiential marketing as a sales strategy that provides customers with a unique, good and memorable emotional understanding. A practical suggestion would imply that paying attention to this variable is more likely to improve customer purchasing decisions on the Go-jek application.